2012
DOI: 10.1177/2150135111431843
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Oxygenation During Initiation of Cardiopulmonary Bypass

Abstract: A controlled oxygenation protocol was associated with significantly lower postoperative CPK-MB levels. Evaluation of other end points including ventilation times requires a study with larger sample size for validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Some have wondered whether there is a third approach between the extremes of using either 100% or 21% oxygen for reoxygenation. Babu et al [ 71 ] compared hyperoxic versus controlled oxygenation in a graded manner during initiation of cardiopulmonary bypass in cyanotic children undergoing cardiac surgery. They achieved controlled reoxygenation by initiating the CPB with an effective F i O 2 of 0.21 and increased it by 0.1 per minute to ultimately achieve an equivalent of 0.6 (PO 2 : 200–300 mmHg) at five minutes.…”
Section: Clinical Evidence For Hyperoxic Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Some have wondered whether there is a third approach between the extremes of using either 100% or 21% oxygen for reoxygenation. Babu et al [ 71 ] compared hyperoxic versus controlled oxygenation in a graded manner during initiation of cardiopulmonary bypass in cyanotic children undergoing cardiac surgery. They achieved controlled reoxygenation by initiating the CPB with an effective F i O 2 of 0.21 and increased it by 0.1 per minute to ultimately achieve an equivalent of 0.6 (PO 2 : 200–300 mmHg) at five minutes.…”
Section: Clinical Evidence For Hyperoxic Injurymentioning
confidence: 99%
“…In addition, the P a O 2 was unclear from their report when they initiated the CPB with an F i O 2 of 0.21. They indicated that to minimize costs, they opted to not use in-line PO 2 monitors for instantaneous PO 2 measurement and instead they increased oxygen levels over a 5-minute period [ 64 , 71 ]. So there are significant limitations to this study; however, this novel approach may go some way to ameliorate concerns about the safety of purely normoxic CPB.…”
Section: Clinical Evidence For Hyperoxic Injurymentioning
confidence: 99%